Transport Media for Live Skin Tissue from Gray-Brocket Deer (Subulo gouazoubira) - Sandoval, Eluzai Dinai Pinto [UNESP]; Duarte, José Maurício Barbanti [UNESP] (SAGE Publications, 2025)
Sampling skin fragments has been an important strategy for genetic studies and ex situ conservation, aiding in the preservation of genetic diversity in Neotropical deer and other wild species. From the moment of collection in the field, transport media must ensure tissue viability by providing the necessary nutrients until laboratory processing for culture or cryopreservation. This study aimed to evaluate the effects of temperature and storage duration on tissue viability and cell growth using two types of skin transport media: Dulbecco’s modified Eagle medium (DMEM) supplemented with 15% fetal bovine serum and 0.9% physiological saline solution. Skin fragments were collected from the inguinal region of five captive gray-brocket deer (Subulo gouazoubira) and divided into small samples, which were randomly assigned to each transport medium. The samples were stored at 5°C and 24°C for 24 and 72 hours, followed by cryopreservation and thawing to assess histomorphology, apoptosis (TUNEL test), cell growth, viability (Trypan blue and MTT assay), and mitotic index. The results showed that physiological saline solution is as efficient as DMEM in maintaining tissue viability, with 80% of viable cells observed and no significant difference after storing in different skin transport media (p > 0.05). Cell morphology and apoptosis did not change in response to media, temperature, or storage duration. We recovered metaphases from all skin tissue storing conditions, with a similar mitotic index to those presented in other cell culture studies from deer biopsies. These results showed the feasibility of storing skin tissue samples during 24 and 72 hours at 5°C and 24°C in different transport media guaranteeing the cell growth and viability for genetic studies and reproductive biotechnologies. The study may contribute to sampling collection in places where displacement with large equipment is limited, allowing the establishment of simplified skin transport protocols as an important step to accessing genetic material from individuals inhabiting isolated localities.
Keywords: animal sampling; cell viability; cervidology; cytogenetics; tissue culture